INFLUENC OF IRRIGATION PERIODS AND ORGANIC FERTILIZER ON TOW RICE VSRIETIES GROWN UNDER THE RSYSTEM OF RICE INTENSIFICATION (SRI) - & Al-Maadhedi, Al-Hasanie; & Al-Maadhedi, Al-Hasanie (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
A field trial was conducted at Al-Mishkhab Rice Research Station at Najaf Governorate during 2015 season to assess the effects of irrigation periods and organic manure on yield and its components of two local rice varieties (Anber 33, Jasmine) under System of Rice Intensification (SRI). The experiment was conducted using split split plot arrangement with RCBD design with three replicates. The main plots were irrigation methods where practiced: continuous submerge and intermittent water application where irrigation water was scheduled at two different intervals 3, 5 days. The sub plots were varieties (anber33,jasmin) and three amount of organic manures 0, 5, 10 ton.haˉ¹, planted under System of Rice Intensification (SRI) compared with conventional method (farmer practice). Transplanted method was done when (SRI) implemented and seedlings were transplanted by pattern square 25×25cm between other with one seedlings per hill and early transplanted 15 days seedling old. The conventional method were closed randomize space (10- 15)cm with more than one (3-5) seedlings, and late transplanted (30 days) seedling old. The results indicated that can be save amount of water and obtain of high yield by 29.5% with less water consumption by 57.6 % was used irrigation intervals of 3 days compared with continuance submerge, and then the amount of water consumption with 3 days interval was 3.67 mm equal 36.762 m³.haˉ¹, with 5 days interval 3.18 mm equal 31.869 m³.haˉ¹, with continuance submerge 8.66 mm equal 86.678 m³.haˉ¹. Also the results indicated that the water use efficiency (WUE) with irrigation interval 5 days was 31869 kg m-³ , with 3 days interval was 36762kg m-³ , with continuous submerge was 86678 kg m-³. The WUE Increase was with 3 days interval 70 %, and then the water consumption was reduced 2.2 compared with continuous submerge. The results indicated that there were significant differences with growth parameters (plant hight, and dry matter weight) and significant differences with yield and its components (Panicle number per m², grain number per panicle, 1000 grain weight, sterile percent, grain yield, and harvest index) when used 3 days intervals and 10 ton.haˉ¹ organic manure.